3-D Visualization on Workspace of Parallel Manipulators - Yoshito TANAKA; Isao YOKOMICHI; Junko ISHII; Toshiaki MAKINO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2009)
In parallel mechanisms, the form and volume of workspace also change variously with the attitude of a platform. This paper presents a method to search for the workspace of parallel mechanisms with 6-DOF and 3D visualization of the workspace. Workspace is a search for the movable range of the central point of a platform when it moves with a given orientation. In order to search workspace, geometric analysis based on inverse kinematics is considered. Plots of 2D of calculations are compared with those measured by position sensors. The test results are shown to have good agreement with simulation results. The workspace variations are demonstrated in terms of 3D and 2D plots for prototype mechanisms. The workspace plots are created with OpenGL and Visual C++ by implementation of the algorithm. An application module is developed, which displays workspace of the mechanism in 3D images. The effectiveness and practicability of 3D visualization on workspace are successfully demonstrated by 6-DOF parallel mechanisms.